Pelatihan Peningkat Minat Belajar Pada Anak Di Sekolah Dengan Metode Diskusi - Tri Ramadani, Nadila; Thamrin, Husni (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
In the era of the rise of online games among underage children which can be freely accessed via mobile phones, and causing children's interest in learning to continue to decline over time. Apart from the fact that online games are increasingly mushrooming among children, the decline in children's interest in learning is also due to a decrease in the learning methods used which are also boring. this is also very visible among children who live in rural areas due to the lack of updating of parents and the existing education system in rural areas, which is still monotonous. This will become a very serious problem if it continues. This also happened to several children in sialang village. because of this the process of providing assistance is also carried out through field work practices or PKL II students of social welfare sciences, Faculty of Social and Political Sciences, University of North Sumatra by applying the discussion method in learning. This method has the aim of increasing children's interest in learning and training children to exchange ideas and learning processes as well as daily activities. Apart from that, a mini project was also carried out at the practicum this time, namely by making an intervention, specifically an intervention that aims to help several children in the unlucky village in solving the problems they are experiencing.